Numerical Study of Stresses around Holes Drilled and Filled by Expansive Cement: Case of Isotropic Linear Elastic Block of Rock - Mambou Ngueyep Luc Leroy; Gael Nkenwoum Chebou (Advances in Materials Science and Engineering)
This work dealt with an essential problem of fragmentation of rocks with expansive cement. The redistribution and magnitude of stresses and displacement generated around holes were done by using Ansys Inc. Code which is based on finite element code. Blocks of rock with one hole, two holes, and nine holes drilled in square mesh and staggered mesh have been considered. Numerical results reveal that many factors can influence the mechanism of fragmentation of a rock by using expansive cement: hole diameter, hole spacing, panel mesh, expansive pressure applied, and the elastic properties of the massif. Stresses and displacements generated globally decrease when spacing holes increase. Normal stresses allow a better stress interaction between holes in the case of square mesh disposition. Staggered mesh disposition generates higher stresses than the square mesh disposition. But the square mesh disposition can be useful for controlled fragmentation in order to obtain block of rock with square geometry. For each expansive cement and rock, there exist suitable range of diameter and spacing hole which can generate high stresses for breaking the rock.